North Padang Lawas District Regulation - Ramadani Siregar; Muhammad Arsad Nasution (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This research is entitled Implementation of North Padang Lawas District Regulation Number 9 of 2016 Article 55 Concerning The Duties, Powers, Rights and Obligations of Village Head in Batang Onang Baru. The formulation of the problem in this research is How is the implementation of the Regional Regulation of North Padang Lawas Regency Number 9 of 2016 Article 55 concerning the duties, powers, rights and obligations of the Village Head, and what are the factors that influence the implementation of the duties and authorities of the Village Head in Batang Onang Baru Village. To obtain the results of this study, the researcher used a descriptive field research type. The data sources in this study were the Batang Onang Baru village apparatus and PKK members and the community. Secondary data in this study is data taken as supporting primary data without having to go directly to the field, including official documents, legal books, journals and articles related to this research. Based on the results of the study, it is known how the implementation of the implementation of the regional regulation of the North Padang Lawas Regency No. 9 of 2016 concerning the duties, authorities, rights and obligations of the village head in Batang Onang Baru. In its implementation it has not been effective because it is not in accordance with the provisions. The factors are that there is no legal counseling on community empowerment that is implemented through PKK, there is no inefficient supervision budget. And the implementation of the duties and authority of the village head in terms of fiqh siyasah, namely at the time of the Prophet, empowerment was carried out through a process of education and the liberation of slaves that all humans were equal in the sight of Allah.